Anesthetic drug wastage in the operation room: A cause for concern - Kapil Chaudhary; Rakesh Garg; Anju R Bhalotra; Raktima Anand; K K Girdhar (Wolters Kluwer Medknow Publications, 2012)
Context: The cost of anesthetic technique has three main components, i.e., disposable supplies, equipments, and anesthetic drugs. Drug budgets are an easily identifiable area for short-term savings. Aim: To assess and estimate the amount of anesthetic drug wastage in the general surgical operation room. Also, to analyze the financial implications to the hospital due to drug wastage and suggest appropriate steps to prevent or minimize this wastage. Settings and Design: A prospective observational study conducted in the general surgical operation room of a tertiary care hospital. Materials and Methods: Drug wastage was considered as the amount of drug left unutilized in the syringes/vials after completion of a case and any ampoule or vial broken while loading. An estimation of the cost of wasted drug was made. Results: Maximal wastage was associated with adrenaline and lignocaine (100% and 93.63%, respectively). The drugs which accounted for maximum wastage due to not being used after loading into a syringe were adrenaline (95.24%), succinylcholine (92.63%), lignocaine (92.51%), mephentermine (83.80%), and atropine (81.82%). The cost of wasted drugs for the study duration was 46.57% (Rs. 16,044.01) of the total cost of drugs issued/loaded (Rs. 34,449.44). Of this, the cost of wastage of propofol was maximum being 56.27% (Rs. 9028.16) of the total wastage cost, followed by rocuronium 17.80% (Rs. 2856), vecuronium 5.23% (Rs. 840), and neostigmine 4.12% (Rs. 661.50). Conclusions: Drug wastage and the ensuing financial loss can be significant during the anesthetic management of surgical cases. Propofol, rocuronium, vecuronium, and neostigmine are the drugs which contribute maximally to the total wastage cost. Judicious use of these and other drugs and appropriate prudent measures as suggested can effectively decrease this cost.